Mehmet Akif Ersoy'un Şiirlerinde Sosyolojik Temalar - Cirhinlioğlu, Zafer; Tektaş, Musa (Muş Alparslan Üniversitesi, 2019)
Themain aim of this study is to try to understand some of sociological approachesin the poems of Mehmet Âkif Ersoy as one of the most known Turkish poets andalso the author of national anthem of Turkey. He was deeply concerned aboutsocial and cultural problems emerged in newly established Turkish Republic.Specifically leaning on the relationship between individual and society heachieved to develop an historical way of analyzing social issues frommultifaceted angles. By this way he tried to combine Eastern wisdom withWestern modernization perspectives. His poems dealt with social and culturalproblems as well as those of each individuals living in the country. On thisbase he also created a way of looking at social problems going on for ages inan ironic manner and criticized them rigorously. Therefore it is possible tosee many kinds of social and cultural realities in his poetry. This perhapsmade him one of the famous, creative and strongest poets in the history ofTurkish society.

Bumakalenin temel amacı Türkiye’de en çok bilinen ve Türk Milli marşını yazanşair olan Mehmet Akif Ersoy’un şiirlerinde ki bazı sosyolojik yaklaşımlarıanlamaya çalışmaktır. Mehmet Akif Ersoy yeni kurulan Türkiye Cumhuriyetindeortaya çıkan toplumsal ve kültürel sorunlar hakkında oldukça kaygılıdır.Özellikle birey ve toplum arasındaki ilişkilere eğilmiş ve geniş bir açıdanbakarak toplumsal meseleleri incelemede tarihsel bir yol geliştirmiştir. Buşekilde Doğu’nun hikmetini Batı’nın estetik modernitesiyle mezcetmeyeçalışmıştır. Şiirleri ülkede yaşayan bireylerin sorunları kadar toplumsal vekültürel sorunlarla da ilişkilidir. Aslında asırlardır devam eden toplumsalsorunları eleştirme ve ironic bir şekilde ele alma yolunu bulmuştur. Onun içinşiirlerinde birçok toplumsal ve kültürel realiteleri bulmak mümküngözükmektedir. Bu özellikleri onu Türkiye tarihinde yer alan en ünlü, yaratıcıve güçlü şairlerinden biri haline getirmiştir.
Sociological Themes in the Poems of Mehmet Akif Ersoy
anemon
Keywords: Mehmet Âkif Ersoy; Sociology; Individual; Society; Human Being; Mehmet Akif Ersoy; Sosyoloji; Birey; Toplum; İnsan